1995
DOI: 10.1016/0896-6273(95)90106-x
|View full text |Cite
|
Sign up to set email alerts
|

CAG expansion affects the expression of mutant huntingtin in the Huntington's disease brain

Abstract: A trinucleotide repeat (CAG) expansion in the huntingtin gene causes Huntington's disease (HD). In brain tissue from HD heterozygotes with adult onset and more clinically severe juvenile onset, where the largest expansions occur, a mutant protein of equivalent intensity to wild-type huntingtin was detected in cortical synaptosomes, indicating that a mutant species is synthesized and transported with the normal protein to nerve endings. The increased size of mutant huntingtin relative to the wild type was highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(90 citation statements)
references
References 29 publications
3
85
0
2
Order By: Relevance
“…Also noteworthy is the Huntington's disease region that, in addition to containing one Alu pair that met the above criterion, also had more Alu pairs that had similar features. This region also contains a multiple trinucleotide repeat at-risk DNA motif (Aronin et al 1995), however, this does not exclude the possibility of another risk factor.…”
Section: Genes and Regions With Alu Arms In The Human Genomementioning
confidence: 98%
“…Also noteworthy is the Huntington's disease region that, in addition to containing one Alu pair that met the above criterion, also had more Alu pairs that had similar features. This region also contains a multiple trinucleotide repeat at-risk DNA motif (Aronin et al 1995), however, this does not exclude the possibility of another risk factor.…”
Section: Genes and Regions With Alu Arms In The Human Genomementioning
confidence: 98%
“…In Ͼ60% of HD patients, increasing length of CAG repeats correlates highly with a decrease in the age of onset of the disease or the extent of striatal degeneration (Persichetti et al, 1994;Aronin et al, 1995;Penney et al, 1997). However, recent findings have reported that the variance in the age of onset of HD could also be attributed to mutations in the gene encoding the GluR6 KAR subunit (Rubinsztein et al, 1997;MacDonald et al, 1999).…”
Section: Abstract: Huntington's Disease; Excitotoxicity; Presynapticmentioning
confidence: 99%
“…Somatic heterogeneity is thought to result in the translation of multiple mutant Huntingtin protein products. Actually, Aronin et al ( 15) reported the existence of somatic mosaicismof Huntingtin protein in brains from HDpatients, and established that the increased size of mutant Huntingtin relative to the wild type was highly correlated with CAGrepeat expansion. The fact that the mosaicism of the mutant protein was found to be more prominent in more pathologically affected brain regions, and that the mosaicism of the mutant protein was found to be greater injuvenile cases than in adult onset cases, is very muchin line with the triplet CAGanalysis.…”
Section: Pathoiogical Assessmentmentioning
confidence: 99%
“…Tissuespecific somatic mosaicismmight be the result of the alteration of cell population related to selective survival and lost neuronal groups in addition to the glial response in certain CNS regions. It was reported that glial cells clearly manifest a high degree of repeat instability (6,15). Some authors have hypothesized that neuronal degeneration and subsequent gliosis could give rise to the somatic mosaicism at both the DNAand protein level (15).…”
Section: Pathoiogical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation